(Re)categorização social e (des)legitimação de discursos: uma análise sociocognitiva de formas referenciais pronominais - Spengler, Ana Cristina Aguiar (2012)
The main objective of this research is to develop a theoretical discussion about the phenomenon of social (re)categorization and (de)legitimation of discourse, in which we take into account social, historical, cultural and cognitive aspects involved in the use of language in times of social conflict. Bearing this objective in mind, we base this study on, at least, three different fields of Linguistics, namely, Critical Discourse Analysis and its studies on (de)legitimation of discourse, Text Linguistics and its contribution with its studies on referentiation and Cognitive Linguistics and the theory of Idealized Cognitive Models. This integration of theories aims at investigating the way the personal pronoun forms of the subjective case turn it feasible to create and reflect the several social categories which may derive from the same pronoun. Besides, we also aim at investigating the role of this linguistic resource in the phenomenon of (de)legitimation of discourse. The socio-historical-cultural moment chosen to study these issues was the Civil Rights of the sixties in the United States of America. The corpus is composed of the speeches I have a dream by Martin Luther King, Jr. and The ballot or the bullet by Malcolm X. In our analysis, we investigate how the two leaders constructed their speeches around (de)legitimation of discourse and of social (re)categorization before the racial conflict the American society faced. We highlight the relation form-meaning established by the pronominal forms as cognitively motivated, lying on beliefs, values and world knowledge shared with and learned from other individuals within the socio-cultural context in which they are inserted.